Correlation Between Mex-Sledai and Mean Platelet Volume In Systemic Lupus Erythematosus Patients - dr. Ayu Paramaiswari,SpPD, K-R; Dody Hendro Susilo; Deddy Nur Wachid Achadiono (Indonesia Rheumatology Association, 2021)
A B S T R A C T Background. Systemic lupus erythematosus (SLE) is a chronic autoimmune disease which has a variety of clinical phenotypes with a complex clinical course. The clinical phenotypes are highly variable which can be characterized by acute attacks, active periods, controllable or remission. Mean platelet volume (MPV) is a straightforward accessible indicator of platelet activity and is associated with systemic inflammation. The routine usage of MPV as markers for disease activity in SLE remains problematic. Early detection of disease progression is pivotal in the management of SLE for obtaining better outcomes. Objective. The study aimed to confirm that the measurement of the disease severity in patients with SLE using Mex-SLEDAI has a negative correlation with the decrease of MPV value. Methods. This cross-sectional analytic descriptive study was conducted using secondary data from the medical records of patients with SLE older than 18 years of age who were not taking antiplatelets in the Internal Medicine policlinic of Dr. Sardjito General Hospital in 2018. Patients with a previous history of cardiovascular and cerebrovascular events, malignancies, receiving a treatment for infections, including sepsis, chronic infections (i.e. tuberculosis, cytomegalovirus, herpes simplex, herpes zoster), HIV, hepatitis B or hepatitis C, and incomplete data of medical record were excluded. The correlation between SLEDAI Mex and MPV values was evaluated using the Spearman's correlation test. Results. Sixty-seven subjects (65 women, 2 men) aged 34 ± 11 years were recruited in the study. The median duration of diagnosis was 38,2 ± 45,7 months. Arthritis, skin rash and photosensitivity were identified in 81,1%, 53,7%, and 46,3% of patients, respectively. The Mex-SLEDAI score ranged from 0 to 16. The average of MPV value is 9.73 ± 1.21 fL. A significant correlation between MPV and SLEDAI Mex was observed (p = 0.03 (p <0.05), r = -0.255). Conclusion. The more severe SLE disease activity (based on the Mex-SLEDAI scoring), the more negative correlation with the MPV value.